Preservation of inscription monuments in Soviet and post-soviet periods - Adamyan, Susanna (History and Culture, 2025)
After the creation of the Armenian alphabet, inscriptions were carved on the walls of historical-architectural monuments, temples and public buildings, which convey important information about the construction of the monument, builders, donations, contracts, etc. Throughout the territory of historical Armenia, there are thousands inscriptions of construction, donation, legal, memorial content have been preserved, the number of which increase every year as a result of construction and agricultural works, archaeological excavations.The collection and preservation of epigaphs became especially important in the 19th century. It has always been in the center of attention of specialists, the state and responsible structures. However, it should be noted that during the Soviet and post-Soviet years, the preservation of these monuments in different regions of the republic was not performed properly, as a result of which the monument lost its historical value.We have tried to present the problem of preservation of epigraphs in Armenia during the centenary.
Keywords: Orbeli; residence; epigaph; tombstone; crosstone; church; topography